2011
DOI: 10.1007/s00467-010-1689-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Insights into Tuberous Sclerosis Complex Renal Disease

Abstract: Patients with tuberous sclerosis complex are at great risk of developing renal lesions as part of their disease. These lesions include renal cysts and tumors. Significant advances in understanding the cell biology of these renal lesions has already led to clinical trials demonstrating that pharmacological interventions are likely possible. This review focuses on the pathology of these renal lesions, their underlying cell biology, and the possible therapeutic strategies that may prove to significantly improve c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 116 publications
(118 reference statements)
0
40
0
1
Order By: Relevance
“…All components of angiomyolipomas, including the vascular cells, immature smooth-muscle-like spindle cells, epithelioid cells, and fat cells contain somatic mutations that, combined with their germline mutation, render the cells deficient in either tuberin or hamartin. Presumably, this deficiency disrupts the integrated control of cell growth leading to the angiomyolipoma [12] . A crosssectional study of TSC patients revealed an increase in angiomyolipomas during childhood and adolescence that then stabilized throughout adulthood [13] .…”
Section: Renal Angiomyolipomas In Tscmentioning
confidence: 99%
“…All components of angiomyolipomas, including the vascular cells, immature smooth-muscle-like spindle cells, epithelioid cells, and fat cells contain somatic mutations that, combined with their germline mutation, render the cells deficient in either tuberin or hamartin. Presumably, this deficiency disrupts the integrated control of cell growth leading to the angiomyolipoma [12] . A crosssectional study of TSC patients revealed an increase in angiomyolipomas during childhood and adolescence that then stabilized throughout adulthood [13] .…”
Section: Renal Angiomyolipomas In Tscmentioning
confidence: 99%
“…Nowadays, the management of active bleeding from angiomyolipomas consists of arterial embolization, sometimes even prophylactic. Unfortunately, most often unnecessarily, partial or total nephrectomy is still performed [8,28].…”
Section: Angiomyolipomamentioning
confidence: 99%
“…The discovery of human melanoma black-45 (HMB-45) and other melanocytic markers such as melanin-A, has increased the reliability of the biopsies. Virtually all angiomyolipomas stain positive for these antibodies, and RCC stains negative, making immunohistochemistry extremely important in excluding RCC [28].…”
Section: Fat-poor Renal Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the relevant literature, TSC may be associated with glial tumors, adenoma sebaceum, rhabdomyoma and hamartomatous tumors of the thyroid, retina, liver, pancreas, lung, kidney, adrenals and ovaries. The clinical manifestations of TSC depend on the target organs, such as the brain, skin, kidneys, lungs and heart, or the organs that are oppressed by the expansion of the lesions (3,9,10).…”
Section: Introductionmentioning
confidence: 99%